Analisis Potensi Pasar Tradisional Temu Sebagai Prosesinteraksi Jual Beli Masyarakat Sekitar Prambon Sidoarjo - Ramzy Ramadhan; Qoni'ah Nur Wijayani (Lembaga Pengembangan Kinerja Dosen, 2024)
Traditional markets are an important element in the economic and social life of communities in various regions of Indonesia, and the Temu Traditional Market around Prambon, Sidoarjo, is no exception. This research aims to carry out an in-depth analysis of the potential of the Temu traditional market as a buying and selling interaction process for the community around Prambon. Through descriptive qualitative research methods, including surveys, interviews and field observations, we explored how this traditional market functions as a center of economic activity and social interaction, as well as how it influences the dynamics of local communities. The results of the research reveal that Temu Traditional Market is not just a place for shopping, but are also important in preserving cultural heritage, supporting people's livelihoods, and encouraging unique social interactions. However, this research also identifies several challenges facing traditional markets, such as changes in consumer tastes and competition with modern shopping centers. Therefore, this research provides important insights for stakeholders and the community in understanding the vital role of the Temu traditional market in supporting economic and social life in the market.